Locating intermedial links with non-filmic network narratives - Tomić, Janica (2009)
The recent decades' upsurge of network narratives (Bordwell) is commonly studied in the context of film history or through what some argue are zeitgeist ties with popular theories of the day (butterfly effect, six degrees of separation, etc.). Sparser intermedial analyses will e.g. focus on historical literary predecessors or the spread of TV series' storytelling logic (or the Internet’ s), but seldom on the parallels with contemporary literary phenomena, such as the boom of Carver/Altman inspired storytelling in 90s neo-realisms, or pervasive cultural theories (e.g. spatial practices in the populist strain of cultural studies). ''Locating media'' refers to two ambitions of this paper, one is to analyze the ways spaces as places of chaotic quotidian interaction are constructed in network narratives and the other is to do so by establishing intermedial links between examples of such structures in Scandinavian and other literary, film and other texts.